111k views
2 votes
Solve the equation 5x^2-6x-7=0

User Bens
by
4.6k points

2 Answers

4 votes

Answer:

x = (3-2√11)/5 ; x= (3+2√11)/5

Explanation:

Δ/4 = (b/2)^2 - ac where b is the term that multiplies x, a is the therm that multiplies x^2 and c is the therm without x

Δ/4 = (-3)^2 - (-7*5) = 9 + 35 = 44 = 2^2 *11

x1 = (3 - √2^2 *11)/5 = (3-2√11)/5

x2 = (3+ √2^2 *11)/5 = (3+2√11)/5

6 votes

Answer:

0.37

Explanation:

5x^2-6x-7=0

25x-6x-7=0

19x-7=0

19x=7

0.37

User Vlado Tesanovic
by
5.0k points